Dekonstruksi Pidana Denda dalam Sistem Peradilan Pidana Anak: Analisis Disharmonisasi - Karina Lira Balqist; Gelar Ali Ahmad (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This article discusses the legal anomalies contained in KMA Decree Number 359/KMA/SK/XII/2022, specifically in the child sentencing template coded Pid.I.A.6.3. The template still accommodates fines for children, which is diametrically opposed to the spirit of Law No.11 of 2012 (the SPPA Law). Using normative legal research methods and a case study approach through Lubuk Pakam District Court Decision No.98/Pid.Sus-Anak/2025/PN Lbp, this study finds that the use of an inharmonious template risks producing a non-executable decision. This article recommends a reconstruction of the decision that prioritizes job training as an independent principal penalty to ensure legal certainty and protect children's constitutional rights.